1994
DOI: 10.1063/1.466791
|View full text |Cite
|
Sign up to set email alerts
|

One- and two-color two-photon resonance enhanced multiphoton ionization spectroscopy of the d 1Σ+ state of NH

Abstract: One-and two-color two-photon resonance enhanced multiphoton ionization spectroscopy of the d?hoofdlettersigmasup+ state of NH Wales, N.P.L.; de Beer, E.; Westwood, N.P.C; Buma, W.J.; de Lange, C.A. Published in:Journal of Chemical Physics DOI:10.1063/1.466791 Link to publication Citation for published version (APA):Wales, N. P. L., de Beer, E., Westwood, N. P. C., Buma, W. J., & de Lange, C. A. (1994). One-and two-color two-photon resonance enhanced multiphoton ionization spectroscopy of the d?hoofdlettersigma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…The latter experiment has been described in detail previously, [32][33][34][35] and only a cursory description is given here, but the Bristol TOF mass spectrometer is newly constructed and replaces our previous REMPI-TOF experiment, so is described in more detail.…”
Section: Methodsmentioning
confidence: 99%
“…The latter experiment has been described in detail previously, [32][33][34][35] and only a cursory description is given here, but the Bristol TOF mass spectrometer is newly constructed and replaces our previous REMPI-TOF experiment, so is described in more detail.…”
Section: Methodsmentioning
confidence: 99%
“…Both experiments have been described in detail previously [51][52][53][54] so only brief summaries of the two experimental methods are given here.…”
Section: Methodsmentioning
confidence: 99%
“…A more complete review of the previous work on electronic spectroscopy can be found in our previous papers. 2,3 Recent experimental [4][5][6][7][8][9][10][11][12][13][14][15][16] and theoretical 17-23 studies have been motivated by applications in astrophysics, [24][25][26][27][28][29][30][31][32][33][34] atmospheric science 35 and chemistry. [36][37][38][39][40][41][42][43] There have been several infrared and far-infrared studies of NH aimed at extracting precise molecular and hyperfine constants in the ground state.…”
Section: Introductionmentioning
confidence: 99%